Wars and child health: Evidence from the Eritrean-Ethiopian conflict - Richard Akresh; Leonardo Lucchetti; Harsha Thirumurthy (Institute for the Study of Labor (IZA), 2011)
This is the first paper using household survey data from two countries involved in an international war (Eritrea and Ethiopia) to measure the conflict's impact on children's health in both nations. The identification strategy uses event data to exploit exogenous variation in the conflict's geographic extent and timing and the exposure of different children's birth cohorts to the fighting. The paper uniquely incorporates GPS information on the distance between survey villages and conflict sites to more accurately measure a child's war exposure. War-exposed children in both countries have lower height-for-age Z-scores, with the children in the war-instigating and losing country (Eritrea) suffering more than the winning nation (Ethiopia). Negative impacts on boys and girls of being born during the conflict are comparable to impacts for children alive at the time of the war. Effects are robust to including region-specific time trends, alternative conflict exposure measures, and an instrumental variables strategy.
urn:nbn:de:101:1-201104133806
Keywords: I12; J13; O12; 330; child health; conflict; economic shocks; Africa; Kinder; Gesundheit; Körpergewicht; Krieg; Eritrea; Äthiopien